On the apparent attenuation in the spatial coherence estimated from seismic arrays. Issue 4 (11th April 2014) - Menon, Ravishankar; Gerstoft, Peter; Hodgkiss, William S.
Abstract : Several recent studies have used the coherence of seismic noise between stations to retrieve the phase slowness and attenuation. However, there is considerable debate on the feasibility of attenuation retrieval, its interpretation, and its dependence on the noise directionality and has been the subject of several analytical and numerical studies. In this article, we perform a detailed analysis of the various factors that play a role in the estimation of spatial coherence and attenuation from seismic arrays using data from the Southern California Seismic Network. For instance, certain common preprocessing steps such as averaging neighboring frequencies to improve the estimate are sufficient to introduce attenuation‐like effects. The presence of first‐mode surface Rayleigh wave and P waves in addition to the fundamental mode in Southern California (at frequencies 0.05–0.2 Hz) suggests that the underlying spatial coherence is better modeled as a linear combination of the above wave types. Although this describes the observed coherence better than a simple zeroth‐order Bessel function, the resulting phase cancelations due to the multiple seismic waves can be misconstrued as attenuation if not taken into consideration. Using simulations, we show that due to the slowness inhomogeneity, azimuthally averaging the coherence is not equivalent to homogenizing the medium and instead introduces apparent attenuation in the coherence due to interference. Trying to fit an exponential decay model to this apparent attenuation results in an attenuation coefficient which is similar to previously published results. Key Points: Averaging is not always helpful in ambient noise processing and can induce bias Higher‐mode Rayleigh and P waves contaminate coherences in the microseism band Attenuation retrieved from data is mostly due to interference and not intrinsic